O Transtorno mental na educação inclusiva: uma experiência com a esquizofrenia na Educação de Jovens e Adultos em Bragança-PA - SILVA, Hanna Rodrigues da (2021)
The right to education for people with disabilities has provided dialogues in different fields. In this sense, the present work addresses as an overall objective an analysis on the education of people with schizophrenia spectrum disorder, as an experience report resulting from the PIBID subproject, carried out in a 1st stage EJA class, in a municipal school in the city of Bragança - Pa. The text discusses situating schizophrenia in the Bragantine educational scenario presenting a documentary survey of the Reference Center in Specialized Therapeutic and Educational Care - Moendy Akã, starting with the arguments of / for the inclusion of schizophrenia through democratic management, the interdisciplinarity of performance teacher, mathematical intervention and the role of the family. Considering, therefore, that the experience in the EJA in relation to the TEE led to a new look at the meaningful learning process for this subject, in this sense, it was necessary to change the pedagogical practices that allowed the student to assimilate the content and, consequently, the their participation in the proposed activity.